2004
DOI: 10.1111/j.1600-0897.2004.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐thyroid Antibodies and Antiphospholipid Syndrome: Evidence of Reduced Fecundity and of Poor Pregnancy Outcome in Recurrent Spontaneous Aborters

Abstract: Thyroid autoimmunity is frequently present in APS recurrent aborters and is often associated with either reduced fecundity or with poor pregnancy outcome. Thyroid antibodies should always be evaluated in women with RSA including those with aPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 23 publications
2
57
0
4
Order By: Relevance
“…Four studies were excluded because TAI status had not been determined (24)(25)(26) or women with TAI had been excluded (27). Three studies were excluded because women with recurrent spontaneous miscarriages had been recruited (28)(29)(30) and another three studies because the IVF outcome had not been recorded or presented (14,31,32).…”
Section: Search Resultsmentioning
confidence: 99%
“…Four studies were excluded because TAI status had not been determined (24)(25)(26) or women with TAI had been excluded (27). Three studies were excluded because women with recurrent spontaneous miscarriages had been recruited (28)(29)(30) and another three studies because the IVF outcome had not been recorded or presented (14,31,32).…”
Section: Search Resultsmentioning
confidence: 99%
“…We included in the TAI group women with both normal and impaired thyroid function in accordance with the idea that the presence of anti-thyroid autoantibodies could represent the main factor leading to an increased risk of reproductive failure even in the absence of clinically overt hypothyroidism. [22][23][24][25][26]35,41,42 In this view, the presence of thyroid autoantibodies can reflect a generalized activation of the immune system with a possible disregulation of local inflammatory process at placental-decidual environment being relevant to the clinical outcome. 26 As increasing maternal age has been reported as an "independent" risk factor for infertility/RSA, we examined the difference in the mean age of women with TAI, SCH, or ET and no significant difference was found between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…The meaning of these interesting findings was in accordance with the evidence supporting the role of thyroid function in the pathogenesis of many autoimmune disorders even in the absence of defined thyroid autoimmunity. 23,42,43 Assuming that infertile/RSA women have an overactive immune system, an increased prevalence of thyroid abnormalities could be expected mainly in terms of autoimmunity (TPO and ATG antibodies). 43 However, we observed that non-autoimmune thyroid dysfunction (such as SCH) is the more frequent condition among the infertile/RSA women and that SCH infertile/RSA women more frequently showed abnormal NK cells than TAI or ET women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [68,69] but not all [70,71], have also found associations between thyroid autoimmunity and increased rates of recurrent miscarriage.…”
Section: Thyroid Auto-immunitymentioning
confidence: 99%